Single treatment of VX poisoned guinea pigs with the phosphotriesterase mutant C23AL: Intraosseous versus intravenous injection. (6th September 2016) - Wille, Timo; Neumaier, Katharina; Koller, Marianne; Ehinger, Christina; Aggarwal, Nidhi; Ashani, Yacov; Goldsmith, Moshe; Sussman, Joel L.; Tawfik, Dan S.; Thiermann, Horst; Worek, Franz
Highlights: I.O. application of C23AL resulted in comparable plasma levels to I.V. application. I.M. application of C23AL did not result in detectable plasma levels within 3 h. C23AL showed lower breakdown of VX in vivo than calculated from in vitro data. Results underline necessity of in vivo experiments in antidote research. Abstract: The recent attacks with the nerve agent sarin in Syria reveal the necessity of effective countermeasures against highly toxic organophosphorus compounds. Multiple studies provide evidence that a rapid onset of antidotal therapy might be life-saving but current standard antidotal protocols comprising reactivators and competitive muscarinic antagonists show a limited efficacy for several nerve agents. We here set out to test the newly developed phosphotriesterase (PTE) mutant C23AL by intravenous (i.v.), intramuscular (i.m.; model for autoinjector) and intraosseous (i.o.; model for intraosseous insertion device) application in an in vivo guinea pig model after VX challenge (∼2LD50 ). C23AL showed a Cmax of 0.63 μmol L −1 after i.o. and i.v. administration of 2 mg kg −1 providing a stable plasma profile up to 180 min experimental duration with 0.41 and 0.37 μmol L −1 respectively. The i.m. application of C23AL did not result in detectable plasma levels. All animals challenged with VX and subsequent i.o. or i.v. C23AL therapy survived although an in part substantial inhibition of erythrocyte, brain and diaphragm AChE was detected. Theoretical calculation of the time required to hydrolyze in vivo 96.75% of the toxic VX enantiomer is consistent with previous studies wherein similar activity of plasma containing catalytic scavengers of OPs resulted in non-lethal protection although accompanied with a variable severity of cholinergic symptoms. The relatively low C23AL plasma level observed immediately after its i.v. or i.o load, point at a possible volume of distribution greater than the guinea pig plasma content, and thus underlines the necessity of in vivo experiments in antidote research. In conclusion the i.o. application of PTE is efficient and resulted in comparable plasma levels to the i.v. application at a given time. Thus, i.o. vascular access systems could improve the post-exposure PTE therapy of nerve agent poisoning.